Knowledge and attitude towards vaccine preventable diseases and vaccination among prospective Malaysian Hajj pilgrims in Klang Valley, Malaysia - Tan, Zhi Han; Mohammed Zamli, Fatin Nor Aisyah; Mohd Iza, Lukman Hariz; Joseph, Narcisse; Mohamed @ Abd Aziz, Nurul Azmawati; Amin Nordin, Syafinaz (Faculty of Medicine and Health Sciences, University Putra Malaysia, 2020)
Hajj is a unique religious mass gathering among Muslims hosted by Kingdom of Saudi Arabia (KSA) annually. It is a fifth pillar that is compulsory to be carried among muslim. Infections due to Neisseria meningitidis, Streptococcus Pneumoniae and Influenza virus are very high among Hajj pilgrims in KSA. Study shows knowledge and attitude towards vaccine preventable disease and vaccination which is very important for the prevention of these infectious diseases. This study aims to determine knowledge and attitude among the prospective Malaysian hajj pilgrims on vaccine preventable disease and vaccination. Method: A cross sectional study was conducted among prospective hajj pilgrims in June 2019. Self-administered questionnaires were given to the respondents through simple random sampling. The socio-demographic characteristics were described using descriptive analysis. Chi-square test was used to analyse the association between the socio-demographic and Malaysian hajj pilgrims’ knowledge and attitude towards the vaccine preventable diseases and vaccination. Results: A total of 135 respondents were recruited in the study. There were statistically significant associations between the knowledge and the highest education level (p=0.01), and also between the knowledge and the occupation (p=0.02) on vaccine preventable disease and vaccination. Conclusion: There is a lack of knowledge among the Malaysian hajj pilgrims about these vaccine preventable diseases and vaccination, especially those who have lower education level and also unemployed. Tabung Haji are highly advised to focus on these group and prepare a special course that focused on these vaccine preventable diseases so that Malaysian Hajj pilgrims will be protected.